2013
DOI: 10.1016/j.pain.2012.10.021
|View full text |Cite
|
Sign up to set email alerts
|

Role of primary somatosensory cortex in the coding of pain

Abstract: The intensity and submodality of pain are widely attributed to stimulus encoding by peripheral and subcortical spinal/trigeminal portions of the somatosensory nervous system. Consistent with this interpretation are studies of surgically anesthetized animals, showing that relationships between nociceptive stimulation and activation of neurons are similar at subcortical levels of somatosensory projection and within the primary somatosensory cortex (in cytoarchitectural areas 3b and 1 of SI). Such findings have l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

11
157
0
3

Year Published

2013
2013
2022
2022

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 212 publications
(178 citation statements)
references
References 138 publications
11
157
0
3
Order By: Relevance
“…The analgesic effect of vibration is likely due to both afferent and cortical processes [64,67,69]. Combining vibratory stimulation with either electrical or thermal stimulation increases the analgesia effect, probably due to the activation and recruitment of multiple types of receptors [30,31,57].…”
Section: Discussionmentioning
confidence: 99%
“…The analgesic effect of vibration is likely due to both afferent and cortical processes [64,67,69]. Combining vibratory stimulation with either electrical or thermal stimulation increases the analgesia effect, probably due to the activation and recruitment of multiple types of receptors [30,31,57].…”
Section: Discussionmentioning
confidence: 99%
“…Zhang et al (2012) also found that high frequency gamma oscillations within SI correlates with the felt intensity of pain, and not merely with the intensity of noxious stimuli. Moreover, lesion studies have confirmed that specific areas in SI were indeed necessary for feeling pain (Cerrato et al (2005); Vierck et al (2013)). Since these cortical structures seem crucial for feeling pain, any entity that lacks a cortex will therefore be unable to feel pain.…”
Section: The No Cortex No Cry Argumentmentioning
confidence: 94%
“…包括感觉-辨别成分又包含情绪-动机成分的多维度复杂体验 (Mathieu, 2016;Bicket, Dunn, & Ahmed, 2016;Huang et al, 2013;Loeser & Treede, 2008;Vaz, Ferreira, Salgado, & Paycha, 2016)。疼痛的感觉-辨别成分, 本身就有一定的警示作用,可促使机体采取保护性的躲避行为 (Vierck, Whitsel, Favorov, Brown, & Tommerdahl, 2013)。然而疼痛除了单纯的感觉外,还具有情感和认知成分,带有强烈的主观色彩 (Xie, Huo, & Tang, 2009)。此外,感觉-辨别主要分析刺激的性质、部位、强度及持续时间等信息,而情感-动机主要与 疼痛产生时的情感和引起的行为密切相关,认知-评估主要与对伤害性刺激的注意、预期和记忆密切相关 (Xie, Huo, & Tang, 2009)。而这种简单的维度区分并不能很好的解释大脑皮层的网络工作在疼痛编码中的 重要作用 (Vierck, Whitsel, Favorov, Brown, & Tommerdahl, 2013)。长期以来,大脑皮层是否涉及到疼痛的 编码存在着一定的争议 (Treede, Kenshalo, Gracely, & Jones, 1999;Disbrow, Buonocore, Antognini, Carstens, & Rowley, 1998;Canavero & Bonicalzi, 2013)。传统观点认为大脑皮层与疼痛感知无关 (Xie, Huo, & Tang, 2009),然而,随着多种现代临床影像技术的诞生,越来越多的研究表明诸多的皮层结构参与疼痛的编码 过程, 如前扣带回皮层(anterior cingulate cortex, ACC)、 岛叶皮层(insular cortex)、 腹外侧眶皮层(ventrolateral orbital cortex, VLO)、运动皮层(motor cortex)、初级躯体感觉皮层(primary somatosensory cortex, S1)以及次 级躯体感觉皮层(secondary somatosensory cortex, S2)等 (Apkarian, Bushnell, Treede, & Zubieta, 2005;Tamaddonfard & Hamzeh-Gooshchi, 2014;Disbrow, Buonocore, Antognini, Carstens, & Rowley, 1998;Xie et al, 2012)。这些皮层结构相应地参与到外侧痛觉系统和内侧痛觉系统中,其中 S1、S2 参与到外侧痛觉系统 中,主要传递疼痛的感觉-辨别信息;ACC、insular 参与到内侧痛觉系统中,主要传递疼痛的情绪信息 (Vierck, Whitsel, Favorov, Brown, & Tommerdahl, 2013;Xie, Huo, & Tang, 2009)。 但是这些脑区在疼痛编码 过程所起的作用还缺乏更加深入的研究,也还没有明确的定论。本文通过整合大量的动物与非侵入性人 类研究来探讨 S1 在疼痛编码过程中的作用, 并针对现有研究的局限, 为今后的研究提供新的思路。 同时, 通过对痛觉神经机制的深入了解,也为以后更高层次的研究提供理论支持。 在动物的研究中,研究者们得出的结论较为一致,认为 S1 主要与疼痛的感觉辨别成分有关,即对疼 痛刺激的部位、 强度、 性质进行编码 (Vierck, Whitsel, Favorov, Brown, & Tommerdahl, 2013;Follett & Dirks, 1994;Guilbaud, Benoist, Levante, Gautron, & Willer, 1992)。然而,与动物研究相比,采用功能性核磁共振 (functional Magnetic Resonance Imaging, fMRI) (Disbrow et al, 1998;Rao et al, 2013)、 正电子发射断层成像 Open Access 技术(Positron Emission Tomography, PET) (Andersson et al, 1997;Casey, Minoshima, Morrow, & Koeppe, 1996;…”
Section: 国际疼痛协会(Iasp)将疼痛定义为"一种不愉快的感觉和情绪体验",这清晰地表明疼痛是一种既unclassified